Priming to Reduce Mand Response Latency - Misbahuddin, Nadia; Mason, L.L. (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
This investigation evaluated the effectiveness of a priming intervention to decrease the latency to mand for a five-year-old boy diagnosed with autism spectrum disorder. Parent participation in clinical applied behavior analytic intervention was increased by providing the family members with a home- and community-based priming technique to increase the efficacy of clinical treatment. Using a multiple-baseline design across settings, mand response latency was analyzed as a function of the verbal behavior priming intervention employed by two different caregivers. Results of the study indicate that the caregiver-implemented priming intervention was successful in reducing the child’s latency to vocalize a request, allowing for more efficient use of instructional time.